High Expression of TIMELESS Predicts Poor Prognosis: A Potential Therapeutic Target for Skin Cutaneous Melanoma - Zhao, Shixin; Wen, Shifeng; Liu, Hengdeng; Zhou, Ziheng; Liu, Yiling; Zhong, Jinbao; Xie, Julin (Frontiers in Surgery, 2022)
Background: Skin cutaneous melanoma (SKCM) is the most lethal skin cancer with an increasing incidence worldwide. The poor prognosis of SKCM urgently requires us to discover prognostic biomarkers for accurate therapy. As a regulator of DNA replication, TIMELESS has been found to be highly expressed in various malignancies but rarely reported in SKCM. The objective of this study was to evaluate the relationship between TIMELESS and SKCM tumorigenesis and prognosis. Methods: We obtained RNA sequencing data from TCGA and GTEx to analyze TIMELESS expression and differentially expressed genes (DEGs). Subsequently, GO/KEGG, GSEA, immune cell infiltration analysis, and protein-protein interaction (PPI) network were used to perform the functional enrichment analysis of TIMELESS-related DEGs. Moreover, the receiver operating characteristic (ROC) curves, Cox regression analysis, Kaplan–Meier (K-M) analysis, and nomograms were applied to figure out the clinical significance of TIMELESS in SKCM. In addition, we investigated the relationship between TIMELESS promoter methylation and SKCM prognosis through the UALCAN database. Finally, the immunohistochemical (IHC) results of normal skin and SKCM were analyzed to determine expression differences. Results: TIMELESS was significantly elevated in various malignancies, including SKCM, and high expression of TIMELESS was associated with poor prognosis. Moreover, a total of 402 DEGs were identified between the two distinct TIMELESS expression groups, and functional annotation showed enrichment with positive regulation of cell cycle and classic oncogenic pathways in the high TIMELESS expression phenotype, while keratinization pathways were negatively regulated and enriched. Further analysis showed that TIMELESS was correlated with infiltration of multiple immune cells. Finally, IHC validated the differential expression of TIMELESS in SKCM. Conclusion: TIMELESS might play a pivotal role in tumorigenesis of SKCM and is closely related to its prognosis.